Palelindon: Unravel the hidden meaning of earthquake - Ida Bagus Agung Wicaksana (Bali Tourism Board, 2019)
On the history of humanity, multiple approaches and methods have been conducted to determine reliable formula on predicting when and where the earth would release its seismic pulse. Many quests have been conducted for more than century to forecast the quake occurrence, yet failed to meet the expectation for long run prediction. Earthquake in a simple term is defined as convulsion on the earth’s surface. Based on its trigger, the quake could be classified into two namely seismic activity and tremor. A vast horseshoe area covers 40,000 km square in the shore of pacific ocean is notorious for its title as The Ring of fire (ROF); an area that has been experiencing continuous series of lithosphere seismic activities. Living within the geologically active area, Bali as part of Indonesia since ancient times seemed to experience multiple quakes. While most research relentlessly sought to predict the earthquake accurately, Balinese local wisdom claimed to be ably predicting the aftereffect of earthquake as compiled in Palelindon manuscript. The script proposed detailed explanation of earthquake effect on nature that subsequently affects human behaviour. This idea may seem as old myth, and could not be suggested publicly worldwide as scientific explanation. Balinese life is firmly bound by local belief and custom. Nevertheless, the text explanation occasionally is taken into account as precaution to prepare any upcoming upheaval on the island.